The model of voter education of women-based democracy volunteers - Hambali, Hambali; Hariyanti, Hariyanti; Eddison, Ahmad (Jurnal Civics: Media Kajian Kewarganegaraan, 2021)
This study aimed at describing the model of voter education of women-based democracy volunteers in Pekanbaru City and Dumai City. Democracy volunteers are partners in the General Election Commission, who deliver electoral information to the public. The voter education model consists of the strategies used, the material delivered, the methods used to provide knowledge, raise awareness, and increase women voters' political participation. This research employed a qualitative approach with descriptive methods"”the informants in this research selected through a non-probability sampling method with a purposive sampling technique. The data validity testing technique used triangulation of data sources. The research findings show that (1) the strategy used was the mapping of target communities and personal communication with community administrators; (2) the material presented included voter requirements, the number of candidates in the 2019 simultaneous elections in Pekanbaru City and Dumai City, introduction of ballot papers, and procedures for voting; (3) the method used was lectures using props in the form of ballots. The female voter is strategic, seeing from the quantity and regulation in Indonesia.